FGF21 mimetic antibody stimulates UCP1-independent brown fat thermogenesis via FGFR1/βKlotho complex in non-adipocytes - Mark Z. Chen; Joshua C. Chang; Jose Zavala-Solorio; Lance Kates; Minh Thai; Annie Ogasawara; Xiaobo Bai; Sean Flanagan; Victor Nunez; Khanhky Phamluong; James Ziai; Robert Newman; et al. (Elsevier, 2017)
Objective: Fibroblast Growth Factor 21 (FGF21) is a potent stimulator of brown fat thermogenesis that improves insulin sensitivity, ameliorates hepatosteatosis, and induces weight loss by engaging the receptor complex comprised of Fibroblast Growth Factor Receptor 1 (FGFR1) and the requisite coreceptor βKlotho. Previously, recombinant antibody proteins that activate the FGFR1/βKlotho complex were proposed to act as an FGF21-mimetic; however, in vivo action of these engineered proteins has not been well studied. Methods: We investigated the mechanism by which anti-FGFR1/βKlotho bispecific antibody (bFKB1) stimulates thermogenesis in UCP1-expressing brown adipocytes using genetically engineered mice. Anti-FGFR1 agonist antibody was also used to achieve brown adipose tissue restricted activation in transgenic mice. Results: Studies with global Ucp1-deficient mice and adipose-specific Fgfr1 deficient mice demonstrated that bFKB1 acts on targets distal to adipocytes and indirectly stimulates brown adipose thermogenesis in a UCP1-independent manner. Using a newly developed transgenic system, we also show that brown adipose tissue restricted activation of a transgenic FGFR1 expressed under the control of Ucp1 promoter does not stimulate energy expenditure. Finally, consistent with its action as a FGF21 mimetic, bFBK1 suppresses intake of saccharin-containing food and alcohol containing water in mice. Conclusions: Collectively, we propose that FGFR1/βKlotho targeted therapy indeed mimics the action of FGF21 in vivo and stimulates UCP1-independent brown fat thermogenesis through receptors outside of adipocytes and likely in the nervous system.